Comparative study on tensile characteristics of friction stir welded aluminium hybrid composite plates. (2022) - Shivanand, H.K.; Sadashiva, M.; Shirahatti, Paraveej; ShivaPrakash, S.
Abstract: The recent promising fields of material development include biomaterials, nanomaterials, smart materials, composites, materials for energy generation and storage along with advanced manufacturing processes. The challenge of developing new material is becoming more interesting. A lot of research work is in progress to fulfill the necessity or requirement for special or advanced engineering materials. This research work prominently concentrated on various parameters of friction welding on low melting aluminium alloy matrix materials constitutes with reinforcement ingredients like E-Glass short fibers and Silicon carbide fine particles and subjected to ASTM standard tensile specimens for unidirectional tensile test, the results should be tabulated and compared.